Unilateral blaschkoid lichen planus - Katarzyna Borowska; Piotr Brzeziński (Our Dermatology Online, 2022)
Lichen planus (LP) is a chronic, inflammatory, autoimmune disease that affects the skin, oral and/or genital mucosa, scalp, and nails. The linear variety of LP can simply be a result of Koebner's phenomenon, segmental LP or zosteriform LP. We present a case of a 55-year-old patient with unilateral blaschkoid lichen planus. LP in a Blaschkoid distribution is rare with only some case reports published till date.